Intraocular Lens Calculations - Aramberri, Jaime; Hoffer, Kenneth J.; Olsen, Thomas; Savini, Giacomo; Shammas, H. John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
Cataract surgery, with 25-30 million surgeries per year, has become one of most popular surgeries in the world. The calculation of its power is of utmost importance. As new premium intraocular lenses (IOLs) and modern surgical techniques have been developed, the demand has grown exponentially - not only for eliminating cataracts, but also for getting rid of the need for glasses. This book offers a comprehensive overview of IOL power calculations and its various formulas and methods. Chapters discuss use of the diagnostic biometry devices that provide the measurements and the management of different clinical situations where particular modifications must be applied. Chapters also discuss the newest generation of multifocal and toric IOLs that can only be implanted if no residual refraction is planned for, which implies a perfect mastery of all the IOL calculation process. This book marks the first time in ophthalmological history that all the main leaders in the field have collaborated in a project that will undoubtedly be the reference for the next ten years. Intraocular Lens Calculations is a must-have resource for cataract and refractive surgeons as well as technicians and anyone dealing with this subject.
Part 1: Introduction -- Chapter 1. The History of the IOL Power Club 2005-2025 -- Chapter 2. American History of IOL Power Calculation -- Part 2: Basic Science -- Chapter 3. Gaussian Optics -- Chapter 4. Exact Optics -- Chapter 5. Pseudophakic Eye Models -- Chapter 6. Data Analysis in IOL Power Calculations -- Chapter 7. Applied eye anatomy: Epidemiology of relevant variables -- Part 3: Measurements -- Chapter 8. Clinical Refraction -- Chapter 9. Ultrasound biometry -- Chapter 10. Optical Biometry -- Chapter 11. Optical Axial Length Measurement -- Chapter 12. Swept Source Biometry -- Chapter 13. ACD, Lens Thickness, and HWTW -- Chapter 14. Corneal Measurement: Keratometry -- Chapter 15. Corneal Measurement; Topography/Tomography -- Chapter 16. The A-Scan Biometer -- Chapter 17. ZEISS IOLMaster 700 -- Chapter 18. Digital solutions in the cataract workflow from Zeiss -- Chapter 19. Biometry Measurements Using A New Large Coherence Length - Swept Source Optical Coherence Tomography -- Chapter 20. Argos Verion image guided system -- Chapter 21. Optical biometer OA2000 -- Chapter 22. ANTERION Swept-source OCT biometer -- Chapter 23. The NIDEK Cataract Suite: The OPD-Scan III Multifunction Diagnostic Device and the AL-Scan Optical Biometer -- Chapter 24. Aladdin optical biometer -- Chapter 25. Haag Streit biometers: Eyestar 900 and Lenstar 900 -- Chapter 26. The Pentacam Family -- Chapter 27. Galilei G6 Lens Professional -- Chapter 28. CASIA2: Anterior Segment 3D Swept Source OCT -- Chapter 29. CSO MS-39: principles and applications -- Chapter 30. IOL Power Calculations with ORA Intraoperative Aberrometer -- Chapter 31 -- Cassini corneal topographer -- Part 4: Calculation Methods -- Chapter 32. An Overview of Intraocular Lens Power Calculation Methods -- Chapter 33. Outcomes review of Intraocular Lens Power Calculation Formulas -- Chapter 34. Lens Power Calculation Formulas -- Chapter 35. Anterior chamber depth and IOL calculations -- Chapter 36. IOL constant optimization -- Chapter 37. Barrett formulas: Strategies to Improve IOL Power Prediction -- Chapter 38. The Castrop IOL formula -- Chapter 39. CSO IOL calculation module -- Chapter 40. Emmetropia Verifying Optical (EVO) Formula -- Chapter 41. The Haigis formula for IOL power calculation -- Chapter 42. Hill-RBF: Improving IOL Power Selection by Artificial Intelligence -- Chapter 43. Hoffer Formulas -- Chapter 44. Holladay formulas -- Chapter 45. Intraoperative aberrometry -- Chapter 46. Kane formula -- Chapter 47. Ladas Super Formula: Origin and evolution with AI -- Chapter 48. Norrby formulas for IOL calculations -- Chapter 49. Okulix ray tracing software -- Chapter 50. The Olsen formula -- Chapter 51. Panacea IOL calculator -- Chapter 52. The PEARL-DGS Formula -- Chapter 53. SRK FORMULA HISTORY -- Chapter 54. The T2 formula -- Chapter 55. The VRF and VRF-G formulas -- Chapter 56. Calculation of phakic and pseudophakic additional lenses -- Chapter 57. Online IOL Power Calculators -- Chapter 58. Power Calculations for Spherical and Toric Phakic IOLs -- Part 5: Toric IOL Calculations -- Chapter 59. Astigmatism notation: Dealing with vectors -- Chapter 60. Astigmatism of the cornea -- Chapter 61. Lens and IOL tilt -- Chapter 62. Toric Calculations -- Part 6: Special Situations -- Chapter 63. Intraocular Lens Power Calculation in Long Eye -- Chapter 64. IOL power calculation in the short eye -- Chapter 65. Post corneal refractive surgery -- Chapter 66. IOL power calculation in keratoconus -- Chapter 67. Patient-specific eye models for intraocular lens power calculation in irregular corneas -- Chapter 68. IOL calculation in vitreoretinal pathology and surgery -- Chapter 69. IOL power calculation in keratoplasty -- Chapter 70. IOL power choice in children -- Chapter 71. Out-of-the-bag implantation IOL power -- Chapter 72. Fellow eye calculation.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Ophthalmology; Ophthalmology